PEMBUATAN CETAKAN SENDOK PUDING DENGAN INJECTION MOLDING DARI MATERIAL POLYLACTIC ACID (PLA) DAN PATI SINGKONG - Al Fath Hasby Ash Shiddiqy, Yhun; Ganda, Andita Nataria Fitri; Wulandari, Diah; Arifianti, Lailatus Sa'diyah Yuniar (Universitas Negeri Surabaya, 2025)
Plastic is widely used in Indonesia, but its non-biodegradable nature causes accumulation and environmental pollution. As a solution, more eco-friendly bioplastics have been developed. This study aims to produce and analyze pudding spoon molds made from Polylactic Acid (PLA) and cassava starch using the injection molding method. The process began with product and mold design using Autodesk Fusion 360 with product dimensions of 125.5 × 25.2 × 2 mm and mold dimensions of 132 × 60 × 35.6 mm. Mold Flow simulation was conducted to analyze parameters such as fill confidence, visual defects, warpage, air traps, and deflection. The mold was manufactured using CNC machining with aluminum 5052 material. The PLA and cassava starch mixtures were varied, heated at a mold temperature of 160 °C and injection temperature of 190 °C, with a cooling time of approximately 5 minutes. The comparison between simulation and actual results showed dimensional differences for each material variation. The largest deviation occurred at a ratio of 40% PLA and 60% cassava starch, reaching 14.9%, while the best result was obtained at a ratio of 50% PLA and 50% cassava starch with only 0.72% deviation from the initial design. This study indicates that material composition significantly affects the dimensional quality of bioplastic products produced through the injection molding process.